2021
DOI: 10.1016/j.nbd.2021.105454
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated clock gene expression and abnormal diurnal regulation of hippocampal inhibitory transmission and spatial memory in amyloid precursor protein transgenic mice

Abstract: Patients with Alzheimer’s disease (AD) often have fragmentation of sleep/wake cycles and disrupted 24-h (circadian) activity. Despite this, little work has investigated the potential underlying day/night disruptions in cognition and neuronal physiology in the hippocampus. The molecular clock, an intrinsic transcription-translation feedback loop that regulates circadian behavior, may also regulate hippocampal neurophysiological activity. We hypothesized that disrupted diurnal variation in clock gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 95 publications
(147 reference statements)
1
17
1
Order By: Relevance
“…Moreover, our data indicate a simultaneous loss of circadian variation of key properties of synaptic mitochondria in early AD, together with a similar loss of the circadian variation of memory performance and LTP magnitude in 3xTg mice. This provides the first demonstration in the 3xTg mouse model of AD, which shows circadian phenotypes more consistent with human AD ( Sheehan and Musiek, 2020 ), of circadian variations of memory and synaptic plasticity that were shown in other AD rodent models ( Baño Otalora et al, 2012 ; Duncan et al, 2012 ; Lanté et al, 2015 ; Stevanovic et al, 2017 ; Petrasek et al, 2018 ; He et al, 2020 ; Fusilier et al, 2021 ) and in Drosophila AD models ( Chen et al, 2014 ; Long et al, 2014 ) and only inferred from proteomic analysis in 3xTg-AD mice ( Bellanti et al, 2017 ).…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, our data indicate a simultaneous loss of circadian variation of key properties of synaptic mitochondria in early AD, together with a similar loss of the circadian variation of memory performance and LTP magnitude in 3xTg mice. This provides the first demonstration in the 3xTg mouse model of AD, which shows circadian phenotypes more consistent with human AD ( Sheehan and Musiek, 2020 ), of circadian variations of memory and synaptic plasticity that were shown in other AD rodent models ( Baño Otalora et al, 2012 ; Duncan et al, 2012 ; Lanté et al, 2015 ; Stevanovic et al, 2017 ; Petrasek et al, 2018 ; He et al, 2020 ; Fusilier et al, 2021 ) and in Drosophila AD models ( Chen et al, 2014 ; Long et al, 2014 ) and only inferred from proteomic analysis in 3xTg-AD mice ( Bellanti et al, 2017 ).…”
Section: Discussionsupporting
confidence: 53%
“…[15][16][17][18][19] Multiple lines of evidence also directly link circadian clocks with AD. 10,11,20 An intact circadian oscillator, containing positive (CLOCK, BMAL1, RORs) and negative (PERs, CRYs, REV-ERBs) core clock components, 21 is required for neuronal maintenance and function, cognitive functions, and behavior. 22 Importantly, circadian disruption by genetic mutations or environmental factors leads to neurodegeneration and impaired cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from our laboratory revealed that sIPSCs onto CA1 pyramidal neurons exhibit diurnal differences and that those diurnal differences are lost in a mouse model of Alzheimer’s Disease (Fusilier et al ., 2021). Here, we replicated and expanded on previous findings by examining sIPSCs in both sexes and conducting additional experiments in the presence of TTX (mIPSCs) to begin to identify pre- and post-synaptic mechanisms contributing to diurnal differences.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in rats found that membrane excitability oscillated across circadian time, with neurons being more depolarized during the subjective late night/subjective early day (Naseri Kouzehgarani et al ., 2020). We recently reported increased nighttime excitability in mouse CA1 pyramidal neuron excitability (Fusilier et al ., 2021). Here, we replicated our previous findings and expanded our study to account for potential sex differences and the influence of the anterior-posterior hippocampal axis.…”
Section: Discussionmentioning
confidence: 99%